Determinantes do silenciamento da questão étnico-racial no Serviço Social brasileiro - Correia, Aline Nascimento Santos (2018)
The objective of this study was to analyze the main determinations that contributed / contributed to silence the ethnic-racial question in the Brazilian Social Service. In coherence with the object of study, a bibliographical research was carried out, of the exploratory type, embodied in dialectical historical materialism. Classifying it as a qualitative analysis, we go through the history of the profession to identify determinations that have silenced the ethno-racial question. In this way, the research was carried out in books, theses, dissertations, articles and magazines. Pursuing the proposed objective, the work starts from the genesis and consolidation of Social Service in Brazil, discusses the advances and limits of the process of renewal of the profession to finally discuss the silencing of the ethnic-racial issue as an expression of structural racism. The results show that the determinations are associated with the conservative professionalization of the Social Service whose attributions turned exclusively to attending to the responses of the State to the social question within the framework of regulated citizenship. This fact implied the distancing of the profession from the segments of the working class that vegetated in informality or, according to Marx (2009, p.746), in the "... army of workers in action, but with a totally irregular occupation." For this reason, the black worker who was mostly in the informality, and outside the regulated citizenship, also remained, for the most part, far from the social policies and actions and reflections of the social worker. The determinations of the process of renewal of Social Service are linked to a conservative base rupture. The rupture with professional traditionalism was shaped by "inclusion" of a critical social theory of Marxist tradition expressed in the minimal curriculum of 1982 and in theoretical maturation noted with the 1996 curriculum revision. Although these processes symbolize a breakthrough for a profession, social theory Marxist in Social Service did not allow a reading of the Brazilian reality based on fundamental aspects of socio-historical formation that made it possible to understand our working class and the social question in Brazil. The main implication of this determination is the silencing of black workers, their working and living conditions, their struggles and confrontations in the Brazilian context and, fundamentally, the silencing in relation to the fact that this is the a major portion of the working class that stands out in the main expressions of the Brazilian social question and, for this reason, is the main user of the services in which the social workers carry out their professional activities. Finally, the persistence of the silencing of the ethnic-racial debate in the profession is, in addition to all the determinations evidenced in the historical context of Social Service, intrinsically associated with structural racism and the mythology of its non-existence in contemporary social relations.